2002
DOI: 10.1046/j.1440-1770.2002.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Present status of submerged macrophyte growth in Lake Biwa: Recent recovery following a summer decline in the water level

Abstract: Whole‐lake areal distribution of submerged macrophyte growth in Lake Biwa was surveyed using aerial photographs in 1994 and 2000, when unusual declines in the water level of approximately 1 m occurred in the dry summers. The estimated total areas of the submerged macrophyte communities were 1441 ha for 1994 and 2825 ha for 2000. In the shallow and eutrophic southern basin, the bottom area covered by vegetation gradually increased year by year after 1994, and the ratio of this area to the total surface area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 13 publications
0
33
1
Order By: Relevance
“…Conversely, due to the time difference of ±5 days in the observed water transparency data and the Landsat-8 image acquisition time, a good agreement between the observed and satellite-derived water transparency was not expected (the obtained R 2 is 0.77). In the south basin of Lake Biwa, the amplified SAV growth is considered as a key driving factor for improved water clarity [22,61]. In this study, the mapped SAV coverage area does not rise as expected, with increased water clarity for the same year.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…Conversely, due to the time difference of ±5 days in the observed water transparency data and the Landsat-8 image acquisition time, a good agreement between the observed and satellite-derived water transparency was not expected (the obtained R 2 is 0.77). In the south basin of Lake Biwa, the amplified SAV growth is considered as a key driving factor for improved water clarity [22,61]. In this study, the mapped SAV coverage area does not rise as expected, with increased water clarity for the same year.…”
Section: Discussionmentioning
confidence: 46%
“…However, with the increase in turbidity the detection reduces to a maximum canopy depth of 0.46 m to 0.5 m. The result further suggests that increased turbidity significantly affects SAV detection. With increased water level in Lake Biwa, it is not possible to detect all the SAV (i.e., canopy depth increases) [22]. In the south basin, based on the in situ survey and previous studies [61], we found that SAV stand height varies (i.e., <0.2 m to >3 m) with location and water depth.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations